2004
DOI: 10.1016/j.bulm.2003.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Control of CNP homeostasis in herbivore consumers through differential assimilation

Abstract: Stoichiometric analysis recognizes that a herbivore is a mixture of multiple chemical elements, especially C, N, and P, that are fixed in various proportions. In the face of a variable quality food supply, herbivores must regulate ingested nutrients to maintain a homeostatic state. We develop a dynamic mathematical model, based on differential assimilation, that controls the C : N and C : P ratios in a herbivore within given tolerance ranges; the actual mathematical mechanism is to define the absorption coeffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Based on animal growth responses to food P content, Boersma and Kreutzer (2002) suggested that Daphnia may not perfectly retain P taken up from food even at low levels of food with high C:P ratios. Nonetheless, since the P release rate tended to decrease with increasing food C:P ratio (e.g., Olsen et al 1986;DeMott et al 1998;Elser and Urabe 1999), it has been often assumed that there is little P release at very high food C:P ratios (e.g., Urabe and Watanabe 1992;Sterner and Elser 2002;Logan et al 2004;Vrede et al 2004;Frost et al 2006). However, according to the model we have presented, the positive relationship between the S P and the growth rate of D. pulicaria cannot be explained without P losses from the internal pool even if P uptake is highly limited.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on animal growth responses to food P content, Boersma and Kreutzer (2002) suggested that Daphnia may not perfectly retain P taken up from food even at low levels of food with high C:P ratios. Nonetheless, since the P release rate tended to decrease with increasing food C:P ratio (e.g., Olsen et al 1986;DeMott et al 1998;Elser and Urabe 1999), it has been often assumed that there is little P release at very high food C:P ratios (e.g., Urabe and Watanabe 1992;Sterner and Elser 2002;Logan et al 2004;Vrede et al 2004;Frost et al 2006). However, according to the model we have presented, the positive relationship between the S P and the growth rate of D. pulicaria cannot be explained without P losses from the internal pool even if P uptake is highly limited.…”
Section: Discussionmentioning
confidence: 99%
“…At least some of these are probably not exclusive to each other (Plath and Boersma 2001;Ravet and Brett 2006). Recently, Boersma and Elser (2006) stressed that excessively P-rich food (low C:P) also had adverse effects on animal growth rates by reducing feeding activities or increasing the metabolic costs for C. In our model, net C gain was assumed to be independent of P gain as long as S P was within an allowable range, and fixed values were applied to a, b, and c for P and C. In reality, these parameters would be functions of absolute or relative elements (Logan et al 2004;He and Wang 2007;Mitra and Flynn 2007) or some biochemical content (growth-essential materials or digestion-resistant substances) in food. This possibility would also explain another discrepancy between the model's output and the experimental observation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This implies both the inclusion of Xexible consumers in stoichiometric models (Grover 2003) as well as evaluating why consumers can maintain lower Xexibility in nutrient content than their plant prey (Logan et al 2004). …”
Section: Grazer Plasticity In Nutrient Contentmentioning
confidence: 99%